Eliminating Radiation Resistance of Non-Small Cell Lung Cancer by Dihydroartemisinin Through Abrogating Immunity Escaping and Promoting Radiation Sensitivity by Inhibiting PD-L1 Expression - Zhang, Hai; Zhou, Fei; Wang, Yingying; Xie, Huikang; Luo, Shilan; Meng, Lu; Su, Bin; Ye, Ying; Wu, Kailiang; Xu, Yaping; Gong, Xiaomei (Frontiers in Oncology, 2020)
Radiation resistance is linked to immune escaping and radiation sensitivity. In this study, we found that the PD-L1 expressions of non-killed tumor cells in NSCLC were enhanced after radiotherapy, and dihydroartemisinin (DHA) could synergistically enhance anti-tumor effect of radiotherapy in NSCLC. A total of 48 NSCLC patients with sufficient tumor tissues for further analyses were enrolled. The PD-L1 expressions of NSCLC were evaluated by immunohistochemistry. Cell apoptosis was measured by flow cytometry and the relationship between the PD-L1 expression and radiation resistance was investigated in patient specimens, xenograft model and cell lines. Firstly, the results indicated that the PD-L1 expression of NSCLC was positively related with the radiation resistance. Secondly, we found that DHA could eliminate the radiation resistance and synergistically enhance anti-tumor effect of radiotherapy in the NSCLC cells lines and xenograft model. Finally, mechanismly, DHA could inhibit the PD-L1 expression to avoid immune escaping by inhibiting TGF-β, PI3K/Akt and STAT3 signaling pathways. In addition, DHA could activate TRIM21 and regulate the EMT-related proteins by inhibiting the PD-L1, so as to enhance the radiation sensitivity and eliminate radiation resistance to NSCLC. Collectively, this study established a basis for the rational design of integrated radiotherapy and DHA for the treatment of NSCLC.